Restorative Possibilities Using Zirconia Ceramics for Single Crowns. - Volz Felberg , Rodrigo (2020)
Two clinical cases are presented to explore technical differences and discusses the advantages and disadvantages of using veneered or monolithic zirconia to manufacture posterior single crowns. The first case describes the clinical steps in manufacturing a monolithic crown on a mandibular left second premolar using high translucency zirconia. It shows the use of a conservative tooth preparation based on the superior mechanical properties that this material presents as well as the final optical characteristics achieved by shading and staining. In the second case, a conventional bilayer restorative treatment was made using zirconia framework followed by veneering with feldspar ceramic on a mandibular left first molar. Recent literature indicates that each of these restorative alternatives presents specific advantages and disadvantages. Factors such as mechanical performance, fracture, esthetic characteristics, clinical success, complication rates, adhesion and antagonist wear performance are discussed comparing the two restorative assemblies. The data highlight that monolithic crowns prevent a major problem reported on bilayer restorations: the chipping of veneering ceramic. Monolithic crowns also allow minimally invasive tooth preparations, thus increasing tooth remnant preservation. However, data that support esthetic performance similarity between monolithic and bilayer assemblies are lacking, thus the predictability of use is restricted for the posterior region, as cases demanding high esthetic appeal continue to fundamentally use bilayer restorations. Failures were not found, and patient satisfaction was reported in both techniques after the 12-month follow up.